2010
DOI: 10.4102/td.v6i1.127
|View full text |Cite
|
Sign up to set email alerts
|

Using a transdisciplinary approach for environmental crisis research in History

Abstract: Although it is true that each local area or region possesses its own historiography – and for that matter its own environmental historiography – there should not be much difference in the research methodology, sources and pitfalls or drawbacks of doing environmental history research in labelled environmental crisis areas. This article presents a concise historiography on dealing with environmental crisis in literature is provided. This is followed by a proposed transdisciplinary (TD)-methodological structure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The poor usually bear a disproportionately heavy burden of the negative externalities caused by environmental mismanagement. 61 It follows from this that the preservation of the environment can confer important benefits on the poor. Shackleton et al demonstrate the often underestimated importance of ecosystem factors such as soil fertility, water resources, eco-tourism, biodiversity, and a range of "cultural services" for the spiritual and material wellbeing of the poor.…”
Section: Economic and Cultural Impacts Of Counterurbanisersmentioning
confidence: 99%
“…The poor usually bear a disproportionately heavy burden of the negative externalities caused by environmental mismanagement. 61 It follows from this that the preservation of the environment can confer important benefits on the poor. Shackleton et al demonstrate the often underestimated importance of ecosystem factors such as soil fertility, water resources, eco-tourism, biodiversity, and a range of "cultural services" for the spiritual and material wellbeing of the poor.…”
Section: Economic and Cultural Impacts Of Counterurbanisersmentioning
confidence: 99%
“…Environmental research projects can be regarded as having progressed to the transdisciplinary 'phase' if they involve researchers from related and unrelated disciplines, non-academic participants (for example user groups, land managers, governmental and non-governmental organizations, and the general public), or professional researchers operating as consultants outside academic institutions. In transdisciplinary research on the human environment or an environmental theme, such as industrial water pollution in area X or Y, academic research is supposed to be 'married' to first-hand experience and knowledge of the focus area under study (compare Van Eeden 2010a;Van Eeden 2010b). Two key justifications for undertaking this kind of participatory research are as follows (Gibbons and Limoges 1994, 153-7;Moran 2002;Klein et al 2001, 35-44):…”
Section: Transdisciplinarymentioning
confidence: 99%
“…In environmental history research, the TD approach also became readily applicable to this field of research because of inevitable connections with communities, their experiences and the wealth of oral history. The many voices, debates and differences in statistical data, together with intellectuals' thinking and debating on environmental ethics, justice, human and legal rights, environmental crime and hydrosolidarity (Jacobs 2003;Van Eeden 2008a), allow environmental history research to be practised from a broader TD angle (as suggested in Figure 1). At least in South Africa, Carruthers noted that: 'there is .…”
Section: Environmental History and Local Environmental Historians On ...mentioning
confidence: 99%